A phase II, randomized, double‐blind, placebo‐controlled, dose‐ranging study to evaluate the efficacy and safety of VT‐1161 oral tablets in the treatment of patients with distal and lateral subungual onychomycosis of the toenail. (1st February 2021) - Elewski, B.; Brand, S.; Degenhardt, T.; Curelop, S.; Pollak, R.; Schotzinger, R.; Tavakkol, A.; Alonso‐Llamazares, Javier; Ashton, Scott J.; Bhatia, Neal; Billings, Michael; Blauvelt, Andrew; et al.
Summary: Background: Onychomycosis is a fungal disease that affects the fingernails and toenails and is predominantly caused by dermatophytes. VT‐1161 is a novel inhibitor of fungal CYP51 through the inhibition of lanosterol demethylase, and has demonstrated potent activity against Trichophyton rubrum and Trichophyton mentagrophytes . Objectives: To evaluate the safety and efficacy of four dosing regimens of orally administered VT‐1161 compared with placebo in patients with moderate‐to‐severe distal and lateral subungual onychomycosis of the toenail. Methods: This was a phase II, randomized, double‐blind, placebo‐controlled, multicentre study (ClinicalTrials.gov identifier NCT02267356). Patients aged 18–70 years ( n = 259) who had 25–75% mycotic involvement were randomized to five treatment groups. They received 300 mg VT‐1161 as a 2‐week daily dose, followed by a once‐weekly dose for either 10 or 22 weeks, or 600 mg VT‐1161 as a 2‐week daily dose, followed by a once‐weekly dose for either 10 or 22 weeks. All treatments were followed by a nontreatment period of 36 weeks. A matching placebo arm was included. Results: In the intent‐to‐treat population, at week 48 the complete cure rates were 0% in the placebo group and ranged from 32% to 42% in the VT‐1161 treatment groups ( P < 0·001 vs. placebo). VT‐1161 was well tolerated, with no evidence of an adverse effect on liver function or QT intervals. Conclusions: VT‐1161 treatment led to high nail clearance rates and a favourable safety profile. VT‐1161 exhibits characteristics that appear promising for the treatment of this chronic and difficult‐to‐treat condition and warrants further evaluation in larger studies.